PROFESIONALISME PEGAWAI DINAS PERUMAHAN RAKYAT, KAWASAN PEMUKIMAN DAN PERTANAHAN (PERKIMTAN) KABUPATEN BANYUASIN DALAM PEMBERIAN REKOMENDASI SIUJK, IMB, PEIL BANJIRâ€ DALAM CEPATNYA MEMBERIKAN PELAYAN - Louwim, Junian (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2018)
This study aims to determine the professionalism of public housing service employees, the regency and settlement area (perkimtan) of banyuasin in giving imb recommendation, piel flood, siujk. This research is a descriptive study with a quantitative approach. The sample of this study consisted of employees and residents as well as developers, respondents who would be chosen unintentionally with a minimum time limit of five days. The sampling technique in this study uses non-probability sampling technique with the type of accidental sampling. Data collection techniques used are: 1) interviews; 3) documentation. Item validity test is done by Product Moment correlation technique from Person. Whereas the results of the study showed that the implementation of the service provided recommendations on the professionalism of public housing officials, the settlement and land area of Banyuasin district in the provision of imb recommendations, piel floods, siujk refers to service standards. The implementation of the public service prime service, the settlement area and the land of Banyuasin Regency can be measured from each of the following indicators: service procedures are categorized clearly, service completion time is categorized quite fast, service costs are categorized as very reasonable, service products are categorized as good, service facilities and infrastructure categorized as very good, the competence of service personnel is categorized as good. Overall the implementation of service standards is still not optimal because there are still service indicators that are still in the sufficient category. Indicators of the implementation of services that are still not well implemented are the aspects of service time.